Computation of static stresses of the head cover bolts in a pump turbine. (March 2019) - Chen, Funan; Chen, Liu; Wang, Zhengwei; Yu, Jixing; Luo, Chengzong; Zhao, Zhiwen; Ren, Shaocheng; Li, Jinwei; Deng, Dezhi
Abstract: The static stress of bolts connecting head cover and stay ring in a pump turbine has been analyzed through ANSYS. The 3D flow of the pump turbine was simulated to get the pressure on head cover and stay ring. The stresses of bolts under 2 loading conditions were calculated: preload only as well as both preload and hydraulic pressure. Results showed that the stress of bolts was greater than head cover and stay ring. Stress concentration of bolts appeared at the position where diameter changed. Due to the influence of hydraulic pressure, the stress of bolts became larger. Head cover and stay ring deformed at the position where stiffness was poor.